2019
DOI: 10.1386/ijcm.12.1.13_1
|View full text |Cite
|
Sign up to set email alerts
|

Music making and the potential impact for a child in foster care

Abstract: The United Kingdom has seen an increasing number of children entering the looked after care system (foster care, adoptive care or residential care). Due to this increasing number, there have been several music projects set up in the United Kingdom, which aim to provide opportunities for musical engagement for looked after children. This article aims to examine the impact that a music project has on children in foster care and their carers. Using a case study strategy to examine the Loud and Clear project based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Lee experienced this phenomenon: '[t]he thing is everyone belongs in the group, and that is why we can unite in such a strong way' (13:79). Dorsey et al 2015), an interactional process within a perceived safe space may offer an experience of connection (Humphrey 2019;Powell 2004).…”
Section: Experiencing Social Harmonymentioning
confidence: 99%
“…Lee experienced this phenomenon: '[t]he thing is everyone belongs in the group, and that is why we can unite in such a strong way' (13:79). Dorsey et al 2015), an interactional process within a perceived safe space may offer an experience of connection (Humphrey 2019;Powell 2004).…”
Section: Experiencing Social Harmonymentioning
confidence: 99%
“…Conn and colleagues (2014) found an association between foster youth involvement in extracurricular physical activity and higher social skills; with those not involved in structured activities scoring higher on measures of depression, loneliness, and substance use. Humphrey (2019) found that foster child participation in music-related activities provided a sense of structure, which facilitated the relationship building process between foster parent and foster child.…”
Section: Introductionmentioning
confidence: 99%
“…Foster parents have a vital role in supporting the development and well-being of foster children who have experienced trauma. Foster child participation in social and extracurricular activities (SEAs) is one method which has been shown to negate the consequences associated with trauma (Humphrey, 2019; Zinn et al, 2017). A study by Kwak et al (2018) found that adolescents in foster care who participated in mentored groups, including athletic and academic clubs, reported higher levels of school engagement and adolescents who participated in art and music clubs reported fewer depression symptoms.…”
Section: Introductionmentioning
confidence: 99%